Neoproterozoic metamorphic events along the eastern margin of the East Sahara Ghost Craton at Sabaloka and Bayuda, Sudan: petrology and texturally controlled in-situ monazite dating - Karmakar, Shreya; Schenk, Volker (Precambrian research, 2015)
Recent geodynamic models for the evolution of the East Sahara Ghost Craton (ESGC) propose delamination of the subcontinental lithospheric mantle due to the formation of Pan-African orogenic belts along its margins. To identify the behavior of the craton's basement during the Neoproterozoic we studied metapelitic rocks from the eastern margin of the craton at Sabaloka and Bayuda, both of which lie about 230km apart along the boundary with the Arabian-Nubian Shield and are considered to be parts of the ESGC. The results are compared to those published for the central part of the craton at Uweinat for a better understanding of the Neoproterozoic tectonic evolution of the craton as a whole. Petrology and texturally controlled in-situ monazite dating reveals that the Sabaloka granulites and the Bayuda metasediments experienced two different metamorphic events. The events at Sabaloka and Bayuda are neither synchronous nor similar in intensity and/or nature, with the events in Bayuda being older than those in Sabaloka and also of lower intensity. At Sabaloka, monazite inclusions in garnet record the timing of an early Neoproterozoic high temperature crustal thickening event at 780-720Ma, while monazite grains in coarse-grained cordierite-spinel symplectites indicate the timing of a Neoproterozoic high to ultra-high temperature overprint at ∼602Ma. Applying the same approach of monazite dating to the pelitic schists from the Dam El Tor fold-and-thrust-belt in the Kurmut Terrane at Bayuda, a crustal thickening event leading to amphibolite-facies metamorphism is dated at ∼890Ma. It was followed by low-grade metamorphism at ∼670Ma leading to recrystallization of matrix minerals. This study thus indicates that the nature and timing of Neoproterozoic tectonometamorphic events along the eastern margin of the ESGC were heterogeneous, both temporally and in their intensity. The ∼890Ma age obtained from the Kurmut Terrane metasediment provides, for the first time, a direct age of the amphibolite-facies metamorphism, slightly later than the magmatism during the Bayudian event dated at 920-900Ma in the Rahaba-Absol Terrane. We infer that tectonism in the juvenile oceanic arc and ophiolitic terranes of the Arabian Nubian Shield (ANS) in the east triggered the end of the passive margin stage of the ESGC and led to the subduction related magmatic-metamorphic Bayudian event. The passive margin stage of the craton further south at Sabaloka seems to have ended later at around 780-720Ma, which may have caused the first high temperature crustal thickening event there. Published magmatic formation ages of 810-806Ma from basalts and ophiolites indicate a rifting stage that formed oceanic re-entrants in the Bayuda and Nubian desert areas along the margin of the craton, subsequent to the Bayudian event. After collision with some of the eastern juvenile ANS terranes the oceanic re-entrants were closed, causing magmatism and a low-grade metamorphic overprint on the amphibolite-facies rocks dated here at ∼670Ma. At Sabaloka, the high-T to UHT granulite-facies decompression event at ∼602Ma and the widespread granitic magmatism all along the eastern margin between 650 and 570Ma was most likely due to the final collision of the ESGC and the ANS. The heterogeneity of Neoproterozoic tectonometamorphic events along the eastern margin of the ESGC thus indicates a local tectonic control on these metamorphic events. In contrast to the eastern margin, no evidence for a metamorphic event during the Neoproterozoic has been found in the center of the craton at Uweinat. The granulites at Uweinat record a Neorchean UHT metamorphism and a Paleoproterozoic UHT reworking. Therefore, it is more likely that the proposed delamination of the subcontinental lithospheric mantle of the entire ESGC was not synchronous and was caused by different orogenic events in different parts of the craton.